Coping and the stages of psychosis: an investigation into the coping styles in people at risk of psychosis, in people with first‐episode and multiple‐episode psychoses. Issue 2 (26th February 2015) - Kommescher, Mareike; Gross, Sonja; Pützfeld, Verena; Klosterkötter, Joachim; Bechdolf, Andreas
Abstract: Aim: The concept of coping is central to recent models of psychosis. The aim of the present paper is to explore whether specific coping styles relate to certain stages of the disorder. Methods: Thirty‐nine clients at clinical high risk (CHR) of first‐episode psychosis, 19 clients with first‐episode psychosis and 52 clients with multiple‐episode psychosis completed a Stress Coping Questionnaire. This questionnaire consists of 114 items defining one overall positive coping scale (with three subscales) and one negative coping scale. Analyses of variance with group as between‐subject factor and coping behaviour as within‐subject factor were used to identify different coping patterns. Results: On the level of subscales no group differences could be detected, but analysis of variance revealed slightly different patterns: CHR clients used significantly more negative than positive coping styles ( P = 0.001), followed by patients with multiple‐episode psychosis ( P = 0.074). First‐episode patients were most likely to use negative as well as positive coping ( P = 0.960). Across all stages of illness, stress control was significantly preferred compared to the other positive coping styles distraction and devaluation. Again, this pattern was especially pronounced for at‐risk clients and patients with multiple‐episode psychosis, whereas patients with first‐episode psychosis were most likely to use devaluation as well as distraction. Conclusions: The overall coping styles were similar across the different stages of psychosis. However, at‐risk persons presented especially pronounced negative coping and a small range of strategies, indicating a specific need for psychosocial support in this stage of the disorder.